2019
DOI: 10.1177/2325958219845419
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Formal and Informal Institutions on ART Drug Adherence

Abstract: A successful antiretroviral therapy (ART) drug adherence is achieved when patients follow their prescribed regimen. This is determined by patient’s motivation that is influenced by resources associated with the patient, society, and relevant institutions. The aim of this study is to assess the impact of formal and informal actors on patients’ ART drug adherence. A qualitative study approach was conducted through face-to-face in-depth interviews of HIV-infected patients and key informants. The analysis was guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
(44 reference statements)
1
4
0
Order By: Relevance
“…This finding agrees with the literature from Ethiopia, Uganda, Kenya, Zimbabwe, and Mozambique, about adults and youth with HIV where again family and friends provided among others, food, money, encouragement and love, and reminders that helped them overcome multiple barriers to ART adherence. 27,67,71,72,75 Consistent with findings from the USA and South Africa among adult and older patients (50+) with HIV [47,68], this study also found that bonding networks, particularly family members, were also key in protecting some of YALWH against stigma and also helped them cope with HIV.…”
Section: Perceived Roles Of Social Networksupporting
confidence: 84%
See 3 more Smart Citations
“…This finding agrees with the literature from Ethiopia, Uganda, Kenya, Zimbabwe, and Mozambique, about adults and youth with HIV where again family and friends provided among others, food, money, encouragement and love, and reminders that helped them overcome multiple barriers to ART adherence. 27,67,71,72,75 Consistent with findings from the USA and South Africa among adult and older patients (50+) with HIV [47,68], this study also found that bonding networks, particularly family members, were also key in protecting some of YALWH against stigma and also helped them cope with HIV.…”
Section: Perceived Roles Of Social Networksupporting
confidence: 84%
“…Likewise, bridging networks of adults with HIV in Ethiopia and Zimbabwe mainly comprised non-formal (indigenous community initiated) groups and rarely formal groups (linked/facilitated by governmental and non-governmental organizations). 67,68,71 This study demonstrates that non-formal community groups may play a supportive role to YALWH on ART in places where formal community groups are scarce, like in Sub-Saharan Africa. 24 Like in a previous study, 23 peer support groups were also found to help YALWH to live positively and come to terms with the HIV disease.…”
Section: Dovepressmentioning
confidence: 73%
See 2 more Smart Citations
“…Evidence from meta-analyses and systematic reviews show that psychosocial interventions are an effective approach to improving ART adherence [12]. Formal and informal institutions play important roles in improving HIV treatment adherence [13]. Our study results are important for developing and adapting a clinic-based intervention that focuses on provider-patient communication.…”
Section: Discussionmentioning
confidence: 81%